ROS1 genomic rearrangements are rare actionable drivers in microsatellite stable colorectal cancer. Issue 12 (30th August 2022) - Akhoundova, Dilara; Hussung, Saskia; Sivakumar, Smruthy; Töpfer, Antonia; Rechsteiner, Markus; Kahraman, Abdullah; Arnold, Fabian; Angst, Florian; Britschgi, Christian; Zoche, Martin; Moch, Holger; Weber, Achim; et al.
Abstract: c‐Ros oncogene 1, receptor tyrosine kinase ( ROS1 ) genomic rearrangements have been reported previously in rare cases of colorectal cancer (CRC), yet little is known about the frequency, molecular characteristics, and therapeutic vulnerabilities of ROS1‐driven CRC. We analyzed a clinical dataset of 40 589 patients with CRC for ROS1 genomic rearrangements and their associated genomic characteristics (Foundation Medicine, Inc [FMI]). We moreover report the disease course and treatment response of an index patient with ROS1 ‐rearranged metastatic CRC. ROS1 genomic rearrangements were identified in 34 (0.08%) CRC samples. GOPC‐ROS1 was the most common ROS1 fusion identified (11 samples), followed by TTC28‐ROS1 (3 samples). Four novel 5′ gene partners of ROS1 were identified ( MCM9, SRPK1, EPHA6, P4HA1 ). Contrary to previous reports on fusion‐positive CRC, ROS1 ‐rearrangements were found exclusively in microsatellite stable (MSS) CRCs. KRAS mutations were significantly less abundant in ROS1 ‐rearranged vs ROS1 wild type cases. The index patient presented with chemotherapy‐refractory metastatic right‐sided colon cancer harboring GOPC‐ROS1 . Molecularly targeted treatment with crizotinib induced a rapid and sustained partial response. After 15 months on crizotinib disseminated tumor progression occurred and KRAS Q61H emerged in tissue and liquid biopsies. ROS1 rearrangements define a small, yet therapeutically actionable molecular subgroup of MSS CRC. In summary, the high prevalence of GOPC‐ROS1 and noncanonical ROS1 fusions pose diagnostic challenges. We advocate NGS‐based comprehensive molecular profiling of MSS CRCs that are wild type for RAS and BRAF and patient enrollment in precision trials. Abstract : What's new? The frequency, molecular characteristics, and therapeutic vulnerabilities of ROS1 ‐driven colorectal cancer remain largely unknown. Using a clinical dataset of 40 589 colorectal cancer patients, here the authors characterize the rare but highly actionable molecular colorectal cancer subgroup harboring genomic rearrangements of the receptor tyrosine kinase ROS1 . They show that GOPC‐ROS1 is the most common ROS1 fusion and that unlike previously‐described fusion oncogenes, ROS1 rearrangements occur exclusively in microsatellite‐stable colorectal cancers. Moreover, they report the treatment course of an index patient, underlining the diagnostic challenge and therapeutic potential of ROS1 targeting in colorectal cancer.